PENENTUAN PRIORITAS PENANGANAN BANJIR GENANGAN BERDASARKAN TINGKAT KERAWANAN MENGGUNAKAN TOPOGRAPHIC WETNESS INDEX Studi Kasus di DAS Solo - Arina Miardini; Grace Serepina Saragih (School of Postgraduate Studies, Diponegoro Univer, 2019)
The increasing frequency of flood events is an indication of the failure of watershed management. Natural resource utilization activities in the Solo watershed tend to be intensive from upstream to downstream, cause a decrease in the carrying capacity of the watershed. To restore the carrying capacity of the watershed, efforts are needed to monitor and evaluate watersheds. The initial stage that needs to be done is to ensure the accuracy of the flood-prone areas by determining priority areas. The purpose of the study is to determine the flood-prone areas in the Solo watershed based on the level of flood vulnerability. Flood vulnerability is influenced by topographic conditions. The Topographic Wetness Index (TWI) method was used to determine the flood-prone areas. The high TWI value indicates that the area has high flood vulnerability and is associated with flat topography with high flow density. This method is based on raster data was derived from DEM 30 m data which is reduced to slope through spatial analysis tools and the accumulation flow is analyzed using Watershed Delineation Tools (WDT). Based on the results of the analysis, the priority of flood handling is determined in the criterion-very vulnerable area with TWI 11.65-38.30 identified as 387098.23 ha (39.68%). Flood handling in the Solo watershed is prioritized on 1) Bojonegoro Regency covering 105215.13 ha, 2) Ngawi (56810.68 ha), 3) Madiun (44102.06 ha), 4) Tuban covering an area of 43072.06 ha, and 5) Ponorogo (35853.62 ha).